Analisis Likuiditas, Solvabilitas, dan Profitabilitas sebagai Indikator Kinerja Keuangan PT Indofood Sukses Makmur Tbk Periode 2019-2023 - M Juni Azka An-nur; Neni Rakhmawati (International Forum of Researchers and Lecturers, 2026)
This study was conducted with the aim of evaluating the dynamics of the financial condition of PT Indofood Sukses Makmur Tbk over a five-year period, namely from 2019 to 2023. This writing applies a quantitative descriptive methodology sourced from secondary data through audited annual financial reports. The main instruments in this data analysis include three pillars of financial ratios: Current Ratio (CR) as a representation of the liquidity aspect, Debt to Asset Ratio (DAR) to measure the level of solvency, and Return on Equity (ROE) as a benchmark for the effectiveness of the company's profitability. Through annual calculations and trend analysis, this study captures the development of the issuer's performance longitudinally. The results of the observation show a significant strengthening in the company's liquidity position, where the Current Ratio jumped from 127% in 2019 to 192% at the end of the 2023 period. In line with that, the solvency profile shows fundamental improvements; Debt reliance, which had reached 51% in mid-2020-2021, was successfully reduced to 46% in 2023. Meanwhile, the company's profitability demonstrated stable resilience, with a consistent ROE of 10% to 13%, despite fluctuations due to operational cost dynamics. Overall, PT Indofood Sukses Makmur Tbk demonstrated excellent financial health through strategic capital and asset management. As a sustainability measure, management is advised to continue optimizing current assets and tightening cost efficiency to secure future profit margins.